(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The compound technological project Croatian Anthropometric System is a national project. The anthropometric measurement of the population of the Republic of Croatia was performed within this project with the aim of adopting the Croatian Anthropometric System as the basic document for the size designation system of clothes and footwear. The measurements of anthropometric characteristics as well as collecting data under social and economic conditions were carried out by previous teams. The successful implementation of this project includes strategic planning, which includes an adequate selection of associates, planning and proper organization, precise distribution of tasks, synchronization of the dynamics of their performances and interactive way of managing the project implementation process. In managing research projects, a strategic management approach also includes the connection and harmonization of diverse knowledge, specific methodologies and specific professional interests of members of a (often multidisciplinary) team of scientific and professional associates, and maintaining the consistency of the methodology of research.